1935
DOI: 10.1001/archotol.1935.00640030055004
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Capillary Plexus in the Scala Tympani

Abstract: A case in which there was an anomalous capillary plexus in the scala tympani of the human cochlea is here reported. The plexus was found in the right ear of a Negro man aged 62. It was located in the basal coil 8.9 mm. within the round window. The condition apparently was unilateral.In the scali tympani, about half way between the basilar membrane and the lower border of the scala, there occurred a union of two capillaries. These capillaries were the vessel under the labium spirale (inner spiral vessel) illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Developmental anomalies of the vasculature of the inner ear have been reported previously (5,9,13,16). Wolff (11) reported a case in which there was an anomalous capillary plexus in the scala tympani of the basal turn. Polvogt and Crowe (10) described 2 cases.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Developmental anomalies of the vasculature of the inner ear have been reported previously (5,9,13,16). Wolff (11) reported a case in which there was an anomalous capillary plexus in the scala tympani of the basal turn. Polvogt and Crowe (10) described 2 cases.…”
Section: Discussionmentioning
confidence: 92%
“…Wolff (11), in an attempt to explain the etiology of inner ear vascular anomalies in fetuses, found that, in a three-month-old fetus, the resorption of mesenchyme, which results in the formation of the peri- plexus (18) while Harris et al (19) noted that macrophages accumulated in the spiral modiolar veins following an infection with the cytomegalovirus. We propose the possibility that selected regions of the inner ear with freely¯oating fenestrated vessels within the scalae could be loci minoris resistentiae that might be selectively more susceptible to infections.…”
Section: Discussionmentioning
confidence: 99%